Dental caries experience in children attending an infant oral health program - Pereira Pinto, Leila Maria Cesário (2010)
Aim: To investigate: a) caries experience in 5 year-old children and its relationship to the caries risk evaluation made before 1 year of age; b) compliance of parents to an infant oral health program as well as the abandonment reasons. Methods: Group A (GA) - 242 children (60-71 months old) who stayed in the program and had been enrolled since their first year of life underwent a clinical examination according to the WHO's criteria; their parents/caregivers were interviewed to ascertain their compliance to the program. Group B (GB) - parents of 60 children, who had dropped out of the program, were interviewed to check the reasons of withdrawing. The caries risk classification was based on the file at the first appointment. Chi-square test was used (α=0.05) for statistical analyses. Results: Most of the children were free of caries (71.1%). Caries risk evaluation showed low sensibility (34.3%, 95% CI = 22.4-46.1) and high specificity (74.4%, 95% CI = 67.6-81.2) to caries experience. Sixty-two mothers (25.6%) reported difficulty to follow the guidelines. The main reason for dropping out was changing to similar health services (40.0%). Conclusions: Caries risk in the first year of life was not efficient to predict dental caries experience at 5 years of age. Educational practice should be improved to increase the compliance of the parents to the program.